Multiculturalismo versus interculturalismo: por uma proposta intercultural do Direito - Eloise da Silveira Petter Damázio (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2008)
The present paper proposes an approach about the concepts of multiculturalism and interculturalism, aims to describe how this analysis contribute with new perspectives to the world of the Legal Science. With respect to multiculturalism, explores its various conceptions and highlights some of the criticisms that are directed, especially in its liberal version. After, considers the interculturalism as a proposal that exceeds the horizon of multiculturalism. Thus, examine the proposal of the philosophy and the intercultural dialogue f rom the philosophical thought of the Raúl Fornet-Betancourt. The paper demonstrates the relevance of the intercultural perspective to the Law, because this means not only a tool that enables criticism of the modern rationality, but also represents an alternative to examine different manifestations of the legal.